Informed Consent as an Effort to Prevent and Resolve Medical Disputes: A Literature Review - A. Ainun Wulandari Nur; Shulhana Mokhtar; Kaisar Razak (Newinera Publisher, 2026)
Informed consent is an important aspect of healthcare practice that aims to ensure patients' rights to obtain information and provide approval for medical procedures to be performed. The implementation of informed consent is not only related to medical ethics but also plays an important role in preventing medical disputes between healthcare providers and patients. Lack of understanding and inadequate implementation of informed consent can increase the risk of conflicts and malpractice claims in healthcare services. This study uses a literature review method conducted by collecting data through journal searches in PubMed, Garuda, and Google Scholar using the keywords: informed consent, medical disputes, medical malpractice, patient legal protection, and health law. This study reviewed 12 research articles relevant to the research topic.